Subprodutos da agroindústria do caju na alimentação de coelhos na fase de crescimento - Gomes, Thalles Ribeiro (2015)
The objective of this research is to determine the chemical composition and digestible energy values of the cashew agribusiness by-products: cashew nut meal (CNM) and the cashew apple dried meal (CADM) and to evaluate the effects of their inclusion in the ration of growing rabbits for performance and carcass characteristics, as well as an economic evaluation. For this, three experiments were carried out, with a metabolism and two performances. In the first experiment were used 36 crossbred rabbits (New Zealand White x Californian), 18 males and 18 females, with 55 days old, in a digestibility trial to determine the nutritional value of CNM and CADM. The rabbits were distributed in a completely randomized design with three treatments and twelve repetitions, being the reference diet and two test diets. In the preparation of the test diet, the evaluated feeds replaced the reference diet in 30% based on dry matter. The digestibility coefficients of dry matter, crude protein and gross energy were, respectively, 76.61 and 67.79; 61.71 and 30.03; 56.53 and 48.61%. The digestible dry matter, digestible protein and digestible energy, based on dry matter, were, respectively, 74.28 and 59.55; 16.97 and 4.76; 3,549 and 2,119 kcal / kg. In each performance trial were used 120 rabbits, 60 males and 60 females, 45 to 90 days old, distributed in a completely randomized design with six treatments and ten repetitions of two rabbits each. In the experiment using the CNM, the treatments were obtained with the addition of CNM at levels of 0, 5, 10, 15, 20 and 25% and it was observed that the inclusion of CNM in levels above 5%, promoted a linear reduction in feed intake and feed conversion, without affecting weight gain and carcass characteristics to the 20% level of inclusion. We also observed a linear reduction in the cost of power per kilogram of weight gain and linear improvement in levels of economic efficiency and cost index. In the experiment using the CADM, treatments were obtained with the inclusion of CADM at levels of 0, 10, 20, 30, 40 and 50% and it was observed that the inclusion of CADM did not influence the feed intake, but promoted a quadratic effect on weight gain and relative meat/bone and worst feed conversion, thus promoting a linear reduction in carcass yield, however, the inclusion of CADM linearly improved economic viability. On the results, it can be said that the cashew nut meal can be included in diets for growing rabbits in levels up to 20%, while the cashew apple dried meal can be included in diets at levels up to 25%.